The Effect of Implementing the Guided Inquiry Learning Model on Students' Critical Thinking Skills at SMA Negeri 20 Bone - Melda, Melda; Adiansyah, Romi; Ali, Muhammad (Magister Pendidikan Biologi, Universitas Negeri Medan, 2023)
Students tend to be unable to control their thinking processes as a result of students' critical thinking abilities being less than optimal. Teachers need to develop learning strategies so that the integration of the learning process in the classroom can take place optimally. This research aims to prove the effect of implementing the guided inquiry learning model on students' critical thinking skills at SMA Negeri 20 Bone. This research uses quantitative research methods with Pre-Experimental Design research type. The results of hypothesis testing using the t-test obtained a significance value smaller than the set significance level of 0.000, meaning a value of 0.000 < 0.05. Research shows that there is a positive influence of implementing the guided inquiry learning model on students' critical thinking skills at SMA Negeri 20 Bone. This research is indirectly able to improve and increase teacher creativity in developing effective learning models.